Pengaruh Fasilitas Kamar dan Harga terhadap Kepuasan Tamu Menginap di Grand Bunda Hotel Bukittinggi - Aidil, Fahril; Suyuthie, Hijriyantomi (Lembaga Yasin AlSys, 2023)
This examination is roused by protests about remaining visitor fulfillment which is affected by room offices and costs at Terrific Bunda Inn Bukittinggi. The reason for this study was to depict room offices and costs on visitor fulfillment and decide the impact of these three factors. The sort of examination utilized is quantitative with a clausal methodology. This exploration was led at Stupendous Bunda Lodging Bukittinggi. Testing in this review was utilizing purposive examining method non likelihood testing type. The sort of data in this study is significant data. This exploration instrument utilizes a study (survey) that has been finished with a Likert scale that has been tried for legitimacy and quality first. This information was dissected utilizing the SPSS form 22.00 program. The consequences of the review are Room Offices fall into a genuinely decent classification with a respondent accomplishment level of 57.65%, Costs with a respondent accomplishment level of 73.25% fall into a decent class and Visitor Fulfillment with a respondent accomplishment level of 75.17% with a decent class. The commitment of Room Offices (X1) and Value (X2) to Visitor Fulfillment (Y) is 16.6% while the excess 83.4% is affected by different elements.